Craniopharyngiomas. - Karavitaki, N; Cudlip, S; Adams, C; Wass, J (2006)
Craniopharyngiomas are rare, mainly sellar/parasellar, epithelial tumors diagnosed during childhood or adult life. Histologically, two primary subtypes have been recognized (adamantinomatous and papillary) with an as yet, unclarified pathogenesis. They may present with a variety of manifestations (neurological, visual, and hypothalamo-pituitary). Despite their benign histological appearance, they often show an unpredictable growth pattern, which, combined with the lack of randomized studies, poses significant difficulties in the establishment of an optimal therapeutic protocol. This should focus on the prevention of recurrence(s), improvement of survival, reduction of the significant disease and treatment-related morbidity (endocrine, visual, hypothalamic, neurobehavioral, and cognitive), and preservation of the quality of life. Currently, surgical excision followed by external beam irradiation, in cases of residual tumor, is the main treatment option. Intracystic irradiation or bleomycin, stereotactic radiosurgery, or radiotherapy and systemic chemotherapy are alternative approaches; their place in the management plan remains to be assessed in adequately powered long-term trials. Apart from the type of treatment, the identification of clinical and imaging parameters that will predict patients with a better prognosis is difficult. The central registration of patients with these challenging tumors may provide correlates between treatments and outcomes and establish prognostic factors at the pathological or molecular level that may further guide us in the future.